A magnetic perturbation GMR-based probe for the nondestructive evaluation of surface cracks in ferromagnetic steels. (April 2016) - Aguila-Muñoz, J.; Espina-Hernández, J.H.; Pérez-Benítez, J.A.; Caleyo, F.; Hallen, J.M.
Abstract: In this paper, a new portable magnetic perturbation probe using a Giant Magneto-Resistance (GMR) sensor to detect and characterize surface cracks in ferromagnetic steels is presented. Measurements from one tangential component of the magnetic flux density are obtained during a single scan over a crack, and two parameters are defined from the output voltage of the GMR sensor: the distance between the peaks, DX, and their voltage difference, DV. The correlations between DX and DV and crack features such as depth, width, and orientation angle are determined. Sensitivity analyses are performed based on the studied features. The probe permits the user to obtain the crack׳s orientation angle using only one measured tangential component of the magnetic flux density. A simple procedure to estimate the crack׳s features is proposed based on the presented analysis. Abstract : Highlights: A new GMR-based magnetic perturbation probe to detect cracks in steel is proposed. The probe is highly sensitive to the width, depth and orientation angle of surface cracks. A simple procedure for the estimation of crack's features is given.